Studies on PIVKA-X - Gaudernack, Gustav; Prydz, Hans (Thrombosis and Haemostasis, 1975)
The incorporation of 14C-glucosamine and 3H-leucine into PIVKA-X and factor X has been studied in Macaca mulatta by means of a monospecific precipitating antiserum. No difference in the incorporation into PIVKA-X and factor X was found.The half-lives of PIVKA-X and factor X were similar (about 30-35 h and 27-31 h respectively) indicating that the vitamin K-induced modifications did not alter the survival of protein.A Russell’s-viper venom/cephalin test system for factor X was more sensitive to inhibition by PIVKA-X than was a tissue thromboplastin-based system.